2011
DOI: 10.1007/s10519-011-9455-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Problem-Solving and Spatial Orientation in the Wolf (Canis lupus) and Dog (Canis familiaris)

Abstract: In this study I tested Benson Ginsburg's theory that dogs should show diminished ability, compared to wolves, in orienting in three-dimensional space and manipulating objects sequentially. Dogs of all ages and juvenile wolves should do poorly on these measures, but at some time before sexual maturity, the juvenile wolves should begin improving to the level of adult wolves. Two adult and seven juvenile wolves were compared with 40 adult German shepherds. The initial task was to pull a single rope suspended from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…However, as the multivariate analysis was a 486 purely exploratory approach, we made our inferences and conclusions based on mixed models. 487 21 When directly comparing wolves' and dogs' persistence in the two tasks using mixed models, our 488 results confirm numerous other studies (Hiestand, 2011;Frank, 2011;Udell, 2015; Marshall-Pescini 489 et al, 2017c,a,b;Rao et al, 2017) that have found wolves to be more persistent than dogs in object 490 manipulation. We found these differences to hold even in the absence of humans during testing, and 491 importantly, with dogs and wolves that have the same level of experience with both, humans and 492 with interacting with different objects.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, as the multivariate analysis was a 486 purely exploratory approach, we made our inferences and conclusions based on mixed models. 487 21 When directly comparing wolves' and dogs' persistence in the two tasks using mixed models, our 488 results confirm numerous other studies (Hiestand, 2011;Frank, 2011;Udell, 2015; Marshall-Pescini 489 et al, 2017c,a,b;Rao et al, 2017) that have found wolves to be more persistent than dogs in object 490 manipulation. We found these differences to hold even in the absence of humans during testing, and 491 importantly, with dogs and wolves that have the same level of experience with both, humans and 492 with interacting with different objects.…”
supporting
confidence: 69%
“…Performing multiple 50 problem-solving experiments over time can help understand consistency in animals' performance and 51 hence, the effect behavioural types have on the correlates of problem-solving success. 52 Dogs and their closest living ancestors, wolves (Frantz et al, 2016) differ strongly in their problem 53 solving success in various paradigms (Frank & Frank, 1982;Frank et al, 1989;Miklósi et al, 2003; 54 Udell, Dorey & Wynne, 2008;Hiestand, 2011;Range & Virányi, 2014; Marshall-Pescini, Virányi & 55 Range, 2015;Udell, 2015;Heberlein et al, 2016;Rao et al, 2017;Brubaker et al, 2017; Marshall-56 Pescini et al, 2017a,b). For instance, wolves were more task-focussed, showed more motor diversity, 57 were more persistent and were able to generalise better than dogs in a string-pulling task (Hiestand, 58 2011).…”
Section: Introduction 23mentioning
confidence: 99%
“…This conclusion is supported by naturally occurring and experimentally induced lesions in the frontal cortex and secondary circuitry remodeling to the limbic system in domestic canines that have demonstrated changes in behavior, probability-based prediction, inhibition, aggression, maintenance, and manipulation of complex learning, and spatial and conceptual memory (Jacobs et al 2003;Christie et al 2008). It has been theorized that wolves use spatial memory and learning to help locate geographically disparate prey (Hiestand 2011). The loss of this faculty would decrease a wolf's ability to seek prey.…”
mentioning
confidence: 89%
“…Studies across taxa have 24 found problem-solving success to depend on several psychological propensities (also referred to as 25 the "correlates of problem-solving success"). These include neophobia (the fear of new situations or 26 objects), motor diversity and flexibility (the repertoire of problem-solving behaviours an animal 27 displays, and its ability to find novel solutions to already known problems, or use known solutions to 28 solve novel problems) and, most importantly, persistence (Lefebvre, Reader & Sol, 2004; Biondi, Bó 29 & Vassallo, 2010;Hiestand, 2011;Cole, Cram & Quinn, 2011;Morand-Ferron et al, 2011; Thornton 30 & Samson, 2012;Benson-Amram & Holekamp, 2012;Griffin & Guez, 2014;Moretti et al, 2015; 31 Griffin & Diquelou, 2015;Huebner & Fichtel, 2015;Udell, 2015;Borrego & Gaines, 2016) (defined 32 as task directed motivation and quantified as the amount of time an animal spends tackling a task). 33…”
mentioning
confidence: 99%
“…We found 539 dogs to be more consistent in their persistence (or lack thereof) and their contact latency than wolves. 540A likely explanation for this could be that selection against persistence (Hiestand, 2011) and direct 541 manipulation of the environment (Moretti et al, 2015;Brubaker et al, 2017) may have resulted in a 542 more consistent reactive-type personality. Wolves, having faced no such selection, may be more 543 variable in their behaviour.…”
mentioning
confidence: 99%